PENGGUNAAN MEDIA VIDEO BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN HASIL BELAJAR IPAS - Tensa Nuraziza Bonde; Said Subhan Posangi; Mifta Huljannah (LPPM IAD Probolinggo, 2026)
This study aims to describe the application of local wisdom-based video media in science learning on the theme of My Region and Its Natural Resources in grade IV of SDN 21 Limboto and improve the science learning outcomes of grade IV students of SDN 21 Limboto through the use of local wisdom-based video media. This type of research is classroom action research. The subjects of this study were grade IV students of SDN 21 Limboto, totaling 26 people, consisting of 10 boys and 16 girls. The data analysis techniques used in this study were qualitative and quantitative analysis. Based on the results of the study, the use of local wisdom-based video media can improve the science learning outcomes of grade IV students of SDN 21 Limboto. This increase can be seen from student learning outcomes in each research cycle. In the pre-cycle stage, the average class score was 68.27 with a learning completion percentage of 46.15%. After the action in Cycle I, the average class score increased to 76.15 with a learning completion percentage of 73.08%. Furthermore, in Cycle II, the average class score increased again to 86.15, with a learning completion percentage of 88.46%. Furthermore, student activity also increased from 75.75% in Cycle I to 91.63% in Cycle II.